Acupuncture in manual therapy - Longbottom, Jennie; ScienceDirect eBooks (Edinburgh ; New York : Churchill Livingstone, 2010)
Acupuncture in Manual Therapy is a comprehensive overview of manual therapy interventions combined with acupuncture management of musculo-skeletal disorders covering all major joints of the body. The book is intended to offer physiotherapists and students of acupuncture a clinical reasoning model, whilst supporting suggested interventions with the relevant evidence base in order to alleviate pain, restore function and facilitate rehabilitation within musculo-skeletal management. It places an emphasis on the neurophysiological processes of pain management stressing the importance of using the correct intervention for the relevant presenting pain mechanism. Each chapter discusses suggested manual intervention, acupuncture evidence and physiological processes underpinning this combined approach to musculo-skeletal pain and dysfunction including meridian acupuncture, auricular acupuncture, electroacupuncture, tens and trigger point acupuncture as a means of addressing the varying pain patterns presented within musculo-skeletal rehabilitation.
This book provides knowledge from distinctive and prominent contributors from the world of manual therapy and acupuncture. This expertise is further supported by the provision of student case studies to offer support and enhance learning. --Book Jacket.
Clinical reasoning in western acupuncture / Lynley Bradnam-Roberts -- Clinical reasoning in traditional Chinese medicine / Jennie Longbottom -- The temporomandibular joint / Allison Middleditch -- Acupuncture in the management of temporomandibular joint disorders / Jennie Longbottom -- Cervical spine / Nick Tucker -- Acupuncture intervention in cervical spine dysfunction / Jennie Longbottom -- The shoulder / Jennie Longbottom -- The Elbow / Jo Gibson -- Acupuncture and elbow dysfunction / Jennie Longbottom -- The Thoracic spine / Jennie Longbottom -- Acupuncture interventions with thoracic spine dysfunction / Jennie Longbottom -- Manual therapy in low back pain / Claire Small -- Acupuncture in low back pain / Jennie Longbottom -- The sacroiliac joint and pelvis / Howard Turner -- Acupuncture within manual therapy / Jennie Longbottom -- The hip / Jennie Longbottom -- Anterior Knee pain / Lee Herrington -- Acupuncture in the management of knee pain / Jennie Longbottom -- Musculoskeletal Injuries in the foot and ankle / Cherye Roche -- Acupuncture in lower limb dysfunction / Jennie Longbottom -- Transcutaneous Electrical Nerve Stimulators for Pain Management / Mark I Johnson.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Acupuncture; Manipulation (Therapeutics); MEDICAL -- Pharmacology; Acupuncture; Manipulation (Therapeutics); Manuele therapie; Acupunctuur; Acupuncture Therapy; Musculoskeletal Manipulations -- methods; Electronic books